Microporous zinc coordination polymer with double interpenetrating structure as well as preparation method and application of microporous zinc coordination polymer

Synthesis of microporous zinc coordination polymers with double interpolation structures by solvent thermal method, and used for fluorescence detection of dimethonidazole, solving the problem of detecting dimethonidazole in the prior art, achieving high selectivity and high sensitivity and ultra-low detection limit detection effect.

CN119431811APending Publication Date: 2025-02-14安徽恒信通智能科技股份有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411416030.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to detect dimethinidazole antibiotics quickly, highly sensitive, selective, miniaturized and practical, especially when the dimethinidazole content in actual samples is small and the coexisting substances are complex.

Method used

A microporous zinc coordination polymer with a double interpolation structure was synthesized by solvothermal method, with the chemical formula of [Zn2(BDC)2(L)]·DMF·11H2O, which was used for fluorescence detection of dimethinidazole. The method includes dissolving the organic ligand H2BDC, bispyridine ligand L and zinc salt in a mixed solvent, performing a solvothermal reaction, and precipitating a bulk crystal after cooling to obtain a microporous zinc coordination polymer.

Benefits of technology

The microporous zinc coordination polymer exhibits high selectivity, high sensitivity and ultra-low detection limit when detecting dimethinazole, and has good anti-interference and repeatability, and can restore its fluorescence intensity by adding salicylic acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431811A_ABST
    Figure CN119431811A_ABST
Patent Text Reader

Abstract

The invention discloses a microporous zinc coordination polymer with a double interpenetrating structure and a preparation method and application thereof, and relates to the technical field of metal-organic framework materials, the chemical formula of the microporous zinc coordination polymer is [Zn2 (BDC) 2 (L)]. DMF. 11H2O, BDC is an organic carboxylic acid ligand, and L is a bipyridine ligand. The microporous zinc coordination polymer with a double interspersing structure and active sites is synthesized by a solvothermal method, and is applied to fluorescence detection of antibiotic dimethyl-nitroimidazole, so that not only are high selectivity, high sensitivity and ultralow detection limit shown, but also the anti-interference performance and repeatability are good, and the application prospect is wide. And the fluorescence intensity can be recovered by adding salicylic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal-organic framework materials, and in particular to a microporous zinc coordination polymer with a double interpenetrating structure and a preparation method and application thereof. Background Art

[0002] Antibiotics have good antibacterial and anti-inflammatory effects and are widely used in animal husbandry and medicine. However, in recent years, the abuse of antibiotics in a large number of aquaculture and medicine industries has brought great hidden dangers to the water and soil environment and human health. Excessive antibiotics accumulate and remain in the soil and water, causing pollution. At the same time, when bacteria acquire drug resistance, it will increase the difficulty of treatment and medical costs for patients. Therefore, antibiotics are also regarded as an environmental pollutant.

[0003] Dimetridazole (DTZ) is a derivative of nitroimidazole, which has anti-anaerobic protozoa and anaerobic bacteria effects and is widely used in clinical treatment of skin infections, respiratory infections and anti-parasites. Therefore, studying the specificity and rapid identification of dimetridazole antibiotics in various samples is of great significance in clinical diagnosis, medicine, food and environmental fields.

[0004] It is urgent to develop a method for rapid and highly sensitive detection of dimetridazole antibiotics. So far, the main detection methods for nitroimidazole antibiotics include high performance liquid chromatography, gas chromatography, liquid chromatography-tandem mass spectrometry, capillary electrophoresis, surface enhanced Raman spectroscopy and enzyme-linked immunosorbent assay. However, expensive instruments, complicated usage methods and the inability to perform real-time monitoring limit the application of these detection methods. In addition, since the content of dimetridazole in actual samples is often very small and the coexisting substances are complex, it is of great practical significance to establish a rapid, highly sensitive, highly selective, miniaturized and practical detection method for the antibiotic dimetridazole.

[0005] Metal-organic frameworks (MOFs) are a class of inorganic-organic hybrid crystalline materials cross-linked by metal ions and organic linkers, which are characterized by highly porous structures. The diversity of MOF design strategies helps to tune their properties, such as surface area, pore size, and functionalization. Since MOFs can incorporate fluorescent groups into their backbone structure, their structures are suitable for luminescent sensing. Luminescent metal-organic frameworks (LMOFs) have flourished in the field of chemical sensing due to their remarkable luminescent properties. The interaction between the LMOF structure and the target analyte can lead to changes in fluorescence emission through mechanisms such as energy transfer, quenching, or emission changes. Due to this responsiveness, LMOFs are ideal candidates for the development of highly sensitive and selective sensors. Recent studies have shown that MOFs are effective sensors for the detection of a variety of antibiotics, including macrolides, penicillins, and tetracyclines. Developments in this field include the development of MOFs with higher stability in various environments, improved fluorescence response, and the ability to function in a variety of environments. The performance of LMOF-based sensors has been further enhanced through functionalization techniques, which has led to significant advances in the accuracy and real-time monitoring of antibiotic detection. Therefore, it is of great theoretical and practical significance to use luminescent metal-organic frameworks to detect antibiotics in the environment and develop new chemical / nanosensing analysis technologies with high selectivity, high sensitivity, miniaturization and strong practicality. At the same time, it has very important application prospects in measuring antibiotic detection, monitoring and governance. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing a microporous zinc coordination polymer. The obtained microporous zinc coordination polymer exhibits high selectivity, high sensitivity and ultra-low detection limit for fluorescence detection of dimetridazole, and has good anti-interference and repeatability.

[0007] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0008] One of the purposes of the present invention is to provide a microporous zinc coordination polymer, the chemical formula of the microporous zinc coordination polymer is [Zn2(BDC)2(L)]·DMF·11H2O, wherein BDC is an organic carboxylic acid ligand and L is a bipyridine ligand.

[0009] The second object of the present invention is to provide a method for preparing the microporous zinc coordination polymer, comprising the following steps:

[0010] (1) dissolving an organic ligand H2BDC, an organic ligand L and a zinc salt in a mixed solvent to obtain a mixed solution;

[0011] (2) subjecting the mixed solution to a solvothermal reaction, cooling, and precipitating block crystals to obtain a microporous zinc coordination polymer.

[0012] The third object of the present invention is to provide the application of the microporous zinc coordination polymer in antibiotic detection, including the detection of antibiotic residues in water.

[0013] The beneficial effects of the present invention are as follows: the present invention synthesizes a microporous zinc coordination polymer having a double intercalated structure and active sites by a solvothermal method, and applies the microporous zinc coordination polymer to the fluorescence detection of the antibiotic dimetridazole, which not only exhibits high selectivity, high sensitivity and ultra-low detection limit, but also has good anti-interference and repeatability, and its fluorescence intensity can be restored by the addition of salicylic acid. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is the coordination mode of the central atom of compound 1;

[0015] Figure 2 It is the binuclear [Zn2(COO)4] structure of the paddle-wheel secondary structural unit of compound 1;

[0016] Figure 3 is the pore structure of compound 1;

[0017] Figure 4 is the PCU topology of compound 1;

[0018] Figure 5 is the infrared spectrum of compound 1;

[0019] Figure 6 is the powder X-ray diffraction pattern of compound 1;

[0020] Figure 7 is the thermogravimetric analysis diagram of compound 1;

[0021] Figure 8 N2 adsorption / desorption isotherms and pore size distribution diagram of compound 1;

[0022] Fig. 9 is the selectivity of compound 1 for antibiotics;

[0023] Fig.10 is the SEM image of compound 1 before and after DTZ detection;

[0024] Fig.11 is the effect of DTZ concentration on the fluorescence intensity of compound 1;

[0025] Fig.12 is the repeatable detection ability of compound 1 for DTZ;

[0026] Fig.13 The detection ability of compound 1 for DTZ under different pH conditions; (a) pH = 5.5, (b) pH = 6.5, (c) pH = 7.5;

[0027] Fig.14 is the anti-interference ability of compound 1 on DTZ detection;

[0028] Fig.15 The effect of adding different organic small molecules on the fluorescence intensity of 1+DTZ system;

[0029] Fig.16 The effect of adding salicylic acid at different concentrations on the fluorescence intensity of the 1+DTZ system. DETAILED DESCRIPTION

[0030] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0031] The invention provides a microporous zinc coordination polymer, the chemical formula of the microporous zinc coordination polymer is [Zn2(BDC)2(L)]·DMF·11H2O, wherein BDC is an organic carboxylic acid ligand, and L is a bipyridine ligand.

[0032] Furthermore, the bipyridine ligand is 2,5-di(4′-pyridine)phenol (L).

[0033] Furthermore, the organic carboxylic acid ligand is terephthalic acid (H2BDC).

[0034] Furthermore, the microporous zinc coordination polymer belongs to the triclinic system, the space group is P-1, and the unit cell parameters are α=89.557(2)°, β=87.042(2)°, γ=75.988(2)°, Z=2.

[0035] Furthermore, the microporous zinc coordination polymer has a double interpenetrating structure and has active sites.

[0036] The present invention provides a method for preparing the microporous zinc coordination polymer, comprising the following steps:

[0037] (1) dissolving an organic ligand H2BDC, an organic ligand L and a zinc salt in a mixed solvent to obtain a mixed solution;

[0038] (2) subjecting the mixed solution to a solvothermal reaction, cooling, and precipitating block crystals to obtain a microporous zinc coordination polymer.

[0039] Furthermore, the zinc salt is zinc acetate dihydrate (Zn(CH3COO)2·2H2O).

[0040] Furthermore, the molar ratio of the organic ligand H2BDC, the organic ligand L and the zinc salt is 1.5:1:2.

[0041] Furthermore, the mixed solvent includes N,N′-dimethylformamide (DMF), acetonitrile (CH3CN), concentrated nitric acid (HNO3) and water (H2O), and the volume ratio of the four is 2.5:0.5:0.05~0.1:0.1~0.25.

[0042] Furthermore, the reaction temperature of the solvent thermal reaction is 100-110° C., and the reaction time is 3-7 days.

[0043] The present invention provides application of the microporous zinc coordination polymer in antibiotic detection, such as detection of antibiotic residues in water.

[0044] Furthermore, the antibiotic is dimetridazole.

[0045] Preparation Example 1

[0046] Add L (24.8 mg, 0.10 mmol), H2BDC (24.9 mg, 0.15 mmol), Zn(CH3COO)2·2H2O (53.1 mg, 0.20 mmol), DMF (2.5 mL) and CH3CN (0.5 mL) into a glass bottle, stir, and drop 2 drops of concentrated HNO3 and 3 drops of H2O to obtain a clear mixed solution; then seal the glass bottle and heat to 108°C for 5 days. After the reaction is completed, cool to room temperature at a cooling rate of 5°C / h. Block crystals precipitate, filter, and dry to obtain a microporous zinc coordination polymer (referred to as compound 1). The yield is 65%. Elemental analysis calculated value (%): C, 42.94; H, 5.01; N, 4.29. Expected value: C, 41.57; H 4.38; N 4.45%.

[0047] Preparation Example 2

[0048] L (24.8 mg, 0.10 mmol), H2BDC (24.9 mg, 0.15 mmol), Zn(CH3COO)2·2H2O (53.1 mg, 0.20 mmol), DMF (2.5 mL) and CH3CN (0.5 mL) were added to a glass bottle, stirred, and 1 drop of concentrated HNO3 and 2 drops of H2O were added dropwise to obtain a clear mixed solution; then the glass bottle was sealed and heated to 100°C for 7 days. After the reaction was completed, the temperature was cooled to room temperature at a cooling rate of 5°C / h. Block crystals were precipitated, filtered, and dried to obtain compound 1. The yield was 67%.

[0049] Preparation Example 3

[0050] L (24.8 mg, 0.10 mmol), H2BDC (24.9 mg, 0.15 mmol), Zn(CH3COO)2·2H2O (53.1 mg, 0.20 mmol), DMF (2.5 mL) and CH3CN (0.5 mL) were added to a glass bottle, stirred, and 2 drops of concentrated HNO3 and 5 drops of H2O were added dropwise to obtain a clear mixed solution; then the glass bottle was sealed and heated to 110°C for 3 days. After the reaction was completed, the temperature was lowered to room temperature at a cooling rate of 5°C / h. Block crystals were precipitated, filtered, and dried to obtain compound 1. The yield was 60%.

[0051] The crystals obtained in Example 1 were washed with DMF until no impurities remained on the surface of the crystals. Crystals with smooth surfaces, regular shapes and suitable sizes were selected for X-ray single crystal diffraction experiments. Mo-Kα rays (λ = 0.07 nm) were purified with a graphite monochromator at room temperature, and then the selected crystals were scanned. The data obtained after crystal diffraction was imported into SHELXL97 software, and the data was processed to obtain the crystal structure. The full matrix least squares method F was used. 2 The structure was refined by correcting the anisotropic temperature factor, isotropic temperature factor, non-hydrogen atom coordinates and hydrogen atom coordinates of the crystal until convergence. The relevant crystallographic data of compound 1 are listed in Table 1.

[0052] Table 1 Crystal data of compound 1

[0053]

[0054]

[0055] The results showed that the compound 1 crystals belonged to the triclinic system with a space group of P-1. The asymmetric unit consisted of two crystallographically independent Zn(II) ions, two deprotonated BDC 2- The two Zn centers have equal distorted square pyramidal geometry, with four O atoms coming from four different BDCs. 2- and one N atom from an L ligand (e.g. Figure 1 ). BDC 2- Each carboxyl group of the linker connects two adjacent Zn(II) atoms in a μ2-bridged manner. 2- The linkers are connected to form a binuclear [Zn2(COO)4] structure with a tetracarboxylic acid paddle wheel secondary building unit (SBU) ( Figure 2 ). Therefore, these SBUs are connected by L into a three-dimensional (3D) network. The 3D framework forms a 1D trapezoidal channel along the A axis ( Figure 3 ), the hole size is Platon analysis showed that the entire anionic framework contained large voids, with each unit cell occupying 38.0% of the volume. From a topological point of view, the BDC linker and the L linker can be considered as 2-connected nodes, while the tetracarboxylic acid paddle wheel SBU can be simplified as a 6-connected node. Therefore, the entire 3D structure of compound 1 can be described as a single node 6-connected PCU topology ( Figure 4 ). However, the overall framework of compound 1 is a two-fold interpenetrating structure. In addition, there are face-to-face π…π interactions between the benzene rings of the BDC ligand and the L ligand. This π…π interaction promotes the electron transfer from the electron-rich substrate to the electron-deficient L ligand, thereby facilitating the sensing reaction.

[0056] The infrared spectrum of compound 1 shows a -1 、580cm -1 、1120cm -1 and 1550cm -1 The weak intensity bands at 1650-1480 cm -1 Characteristic absorption bands in the range of - Group stretching vibration ( Figure 5 ).

[0057] It is well known that the stability of MOFs is crucial for evaluating their sensing potential. In order to determine the stability of compound 1, the present invention performed powder X-ray diffraction (PXRD) analysis on compound 1 ( Figure 6 ). The results show that compound 1 has a well-ordered crystal structure. The PXRD pattern simulated according to the crystal structure data is very consistent with the PXRD pattern of the synthesized sample, which confirms the phase purity of compound 1. And even after multiple cycles of experiments, the crystallinity of compound 1 is not lost, which shows that compound 1 has good durability and stability.

[0058] The present invention evaluated the thermal stability of compound 1 by thermogravimetric analysis (TGA). Figure 7 The initial weight loss observed before 250 °C is attributed to the removal of interstitial water and DMF molecules, and the subsequent weight loss at 280–380 °C is attributed to the decomposition of the organic ligand components. The minimum weight loss is observed above 300 °C, indicating the stability of the ZnO residue due to its high melting point.

[0059] From the N2 adsorption / desorption isotherm ( Figure 8 a) Calculated, due to interpenetration, the BET value of compound 1 is 27.35m 2 / g. In addition, the pore size distribution of compound 1 is as follows Figure 8 As shown in b.

[0060] Application Example 1

[0061] The detection of compound 1 on various commonly used antibiotics, including dimetridazole (DTZ), nitrofuracil (NFT), sulfadiazine (SDZ), sulfamethoxazole (SMT), thiamphenicol (THI), sulfadimethoxine (SMZ), furazolidone (FZD), indomethacin (IMC), ciprofloxacin (CIP), ibuprofen (IPF) and lamotrigine (LMG). 5 mg of compound 1 was dispersed in 5 mL of water, and 40 ppm of antibiotics were added to measure the fluorescence intensity of the solution before and after the addition of antibiotics. Each experiment was repeated 3 times. The quenching efficiency was calculated according to the following formula:

[0062] Quenching efficiency = [(I0-I) / I0] × 100%

[0063] Among them, I0 and I are the fluorescence intensity of the solution before and after the addition of antibiotics, respectively.

[0064] from Fig. 9 It can be seen that after adding different antibiotics, the fluorescence intensity of the solution changes differently. With the addition of DTZ, the fluorescence intensity drops sharply, indicating that compound 1 has a significant quenching effect on DTZ.

[0065] By comparing the SEM images of compound 1 before and after DTZ detection, it can be seen that the structural morphology of compound 1 remains stable ( Fig.10 ).

[0066] In order to further study the quenching effect of compound 1 on DTZ, the present invention conducted a fluorescence titration experiment on a continuous concentration gradient. In order to illustrate the effect of increasing DTZ content on the fluorescence intensity of compound 1, the relationship between the luminescence intensity (I0 / I) and the DTZ concentration was studied ( Fig.11 a), the results showed that the DTZ concentration was as high as 1×10 -4 The linear relationship of M Fig.11 b) This linear relationship reflects the Stern-Volmer equation, which is a well-known model for characterizing quenching phenomena and is expressed as I0 / I=1+K v [DTZ]. Where I0 and I are the fluorescence intensity of the solution before and after DTZ addition, respectively, and K v is the quenching constant, and [DTZ] is the DTZ concentration. The linear behavior between I0 / I and DTZ concentration and its consistency with the Stern-Volmer equation confirm the quenching effect of DTZ on the luminescence of compound 1.

[0067] The calculation shows that the quenching constant of compound 1 for DTZ is 8.86×10 3 M -1 , with a high correlation coefficient of 0.9916 ( Fig.11 b), the minimum detection limit LOD is 1.47×10 -5 M, indicating that compared with most other existing methods and materials for detecting antibiotics, compound 1 has a high sensitivity for detecting DTC. More importantly, the detection process is efficient, because adding DTZ to the compound 1 solution will cause its fluorescence to be almost completely quenched within a few seconds, indicating that compound 1 exhibits rapid responsiveness, outstanding sensitivity and excellent selectivity as a fluorescent sensor for DTZ. In addition, the present invention also conducts a recovery test to further evaluate the repeatability of compound 1. The compound 1 solution after detecting DTZ is continuously centrifuged and washed, and its emission intensity remains almost unchanged after five cycles compared with the initial sample ( Fig.12 ).

[0068] The effect of pH on DTZ detection was studied by conducting experiments at three different pH values ​​(5.5, 6.5, and 7.5). The results showed that compound 1 showed good detection ability at all three pH values. The calculated detection limits were 1.89×10 -5 M and 3.2×10 -4 M. Therefore, the optimum pH is 6.5 ( Fig.13 ).

[0069] In order to study the effect of other antibiotics on fluorescence intensity, the present invention also conducted a competition experiment. When other interfering antibiotics were added to the mixed solution of compound 1 and DTZ (referred to as 1+DTZ system), the quenching effect of compound 1 on DTZ was not affected by other interfering antibiotics ( Fig.14 ), so compound 1 has a good anti-interference effect on DTZ in water, which further illustrates that compound 1 has a high selectivity for DTZ.

[0070] The addition of DTZ can quench the fluorescence of compound 1 without damaging its structural integrity ( Figure 6 ), this property provides compound 1 with an opportunity to restore the fluorescence intensity. -4 M hydroquinone (HQ), salicylic acid (SA), 4-hydroxybenzoic acid (PHA), 4-aminosalicylic acid (PAS), and 3-hydroxybenzoic acid (IHA) solutions were added to the 1+DTZ system, and the fluorescence intensity of the system with SA was significantly restored ( Fig.15). The fluorescence intensity of the 1+DTZ system gradually increases with the increase of SA concentration, and the fluorescence intensity of the 1+DTZ system is least affected by other acids. When other acids are added to the 1+DTZ system, the fluorescence intensity of the system is not greatly affected. The titration method was used to observe the results. When the SA concentration was as high as 1.93×10 -4 M, the fluorescence intensity was fully restored ( Fig.16 ). These results indicate that the 1+DTZ system with systematic design is a promising colorimetric probe for the detection of salicylic acid.

[0071] In summary, the present invention synthesized a novel three-dimensional intercalated zinc metal-organic framework compound by solvothermal method, and studied the fluorescence sensing of DTZ by the compound. It is worth noting that the compound showed an extremely low detection limit of 1.47×10 -5 M. Furthermore, the compound still has a fluorescence sensing effect after five consecutive cycles of sensing DTZ, indicating that its sensing of DTZ is repeatable. In addition, the addition of SA can restore the fluorescence intensity of the compound. These research results indicate that the compound has important application prospects in the fields of environmental monitoring, health quality control, etc.

[0072] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A microporous zinc coordination polymer, characterized in that: The chemical formula of the microporous zinc coordination polymer is [Zn2(BDC)2(L)]·DMF·11H2O, wherein BDC is an organic carboxylic acid ligand and L is a bipyridine ligand.

2. The microporous zinc coordination polymer according to claim 1, characterized in that: The bipyridine ligand is 2,5-di(4′-pyridine)phenol.

3. The microporous zinc coordination polymer according to claim 1, characterized in that: The organic carboxylic acid ligand is terephthalic acid.

4. The microporous zinc coordination polymer according to claim 1, characterized in that: The microporous zinc coordination polymer belongs to the triclinic system, the space group is P-1, and the unit cell parameters are α=89.557(2)°, β=87.042(2)°, γ=75.988(2)°, Z=2.

5. The microporous zinc coordination polymer according to claim 1, characterized in that: The microporous zinc coordination polymer has a double interpenetrating structure and an active site.

6. The method for preparing the microporous zinc coordination polymer according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) dissolving an organic ligand H2BDC, an organic ligand L and a zinc salt in a mixed solvent to obtain a mixed solution; (2) subjecting the mixed solution to a solvothermal reaction, cooling, and precipitating block crystals to obtain a microporous zinc coordination polymer.

7. The method for preparing a microporous zinc coordination polymer according to claim 6, characterized in that: The zinc salt is zinc acetate dihydrate; Preferably, the molar ratio of the organic ligand H2BDC, the organic ligand L and the zinc salt is 1.5:1:2; Preferably, the mixed solvent comprises N,N′-dimethylformamide, acetonitrile, concentrated nitric acid and water, and the volume ratio of the four is 2.5:0.5:0.05-0.1:0.1-0.

25.

8. The method for preparing a microporous zinc coordination polymer according to claim 6, characterized in that: The reaction temperature of the solvent thermal reaction is 100-110° C., and the reaction time is 3-7 days.

9. Use of the microporous zinc coordination polymer according to any one of claims 1 to 5 in antibiotic detection.

10. The use according to claim 9, characterized in that: The antibiotic is dimetridazole.